Formic acid dehydrogenation over Pd NPs supported on amine-functionalized SBA-15 catalysts: structure-activity relationships - Koh, Katherine; Jeon, Mina; Yoon, Chang Won; Asefa, Tewodros (ROYAL SOC CHEMISTRY, 2017)
Palladium nanoparticles (Pd NPs) supported on organoamine-functionalized SBA-15 mesoporous silica are known to have higher catalytic activity for formic acid dehydrogenation than Pd NPs supported on plain, unmodified SBA-15 mesoporous silica. The organoamine groups present around the Pd NPs play important roles in stabilizing the Pd NPs, providing strong metal-molecular support interaction (SMMSI) to the Pd NPs, and rendering enhanced catalytic activities to the materials toward formic acid dehydrogenation. However, detailed studies on the effects of different types of amine groups on the catalytic activities of mesoporous silica-supported Pd NPs toward formic acid dehydrogenation have not been reported. Herein, we describe the synthesis of SBA-15 mesoporous silica grafted with three types of organoamine groups (primary, secondary, and tertiary amine), which are further decorated with tetraamminepalladium(II) complexes that are then reduced to Pd NPs in situ with 10% of H-2/N-2 at 250 degrees C. The effects of the different compositional and steric properties associated with the amine groups on (i) the electronic properties of the Pd NPs, (ii) the size of the Pd NPs, and (iii) the structure-property relationships of the materials were closely examined. Based on the results, the materials' catalytic activities toward dehydrogenation of formic acid to generate hydrogen (H-2) for fuel cells were determined.